Exploring the Mastery Level of Critical Thinking and Problem Solving Skill Among the Technical Undergraduate - Lee, Ming Foong; Mohd Sohod, Siti Nooridayu; Ab Rahman, & Azmanirah (Journal of Technical Education and Training, 2018)
Statistics from the Department of Statistics showed that 76200 graduates in this country still failed to get a job. One of the main reasons of this phenomenon is the graduates are still unable to meet the demand of the current job market. The current job market is not only take seriously on knowledge and technical skills but also soft skills. Therefore, the Ministry of Higher Education (MOHE) listed seven soft skills that should be possessed by the graduates. Among the seven soft skills, critical thinking and problem solving is the one of the emphasized skill. In this skills, there are three main subskills must be mastery from a total number subskills of seven. Thus, a survey was conducted to identify the level of critical thinking and problem solving skills among the engineering undergraduate students. A total of 341 final year students of Bachelor's degree in Universiti Tun Hussein Onn Malaysia were stratified randomly selected as respondents. Data was collected through an achievement test on critical thinking and problem solving skills. Mean, standard deviation, Mann Whitney U test and Kruskal Wallis Test were employed to analyze the gathered data. Results showed that the level of critical thinking and problem solving skills of students for the three main subskills (Ability to Identify and Analyse Problem in Complex or Ambiguous Situation and Develop Justification Evaluation; Ability to Improve and Develop  Thinking Skill as Explain, Analyse and Discussion Evaluated; Ability to Generate  the Ideas and Alternative Evaluation) were at a moderate level. As the conclusion, the MOHE, education institutions and students must work together in order to enhance the acquisition for critical thinking and problem solving skill of graduates through the modification of teaching strategies, strengthening academic programs and others intervention programme.